THE EFFECT OF FORWARD LEAN POSITION AND PURSED LIP BREATHING ON PEAK EXPIRATORY FLOW IN ACTIVE SMOKER - Lutfia Zein Amalia; Erna Setiawati; Rahmi Isma Asmara Putri (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Chronic exposure to tobacco smoke cause activation of macrophages which contribute to the release of inflammatory mediators and the establishment of Chronic Obstructive Pulmonary Disease (COPD). In COPD, the airway become narrowed and result in reduced peak expiratory flow (PEF). One form of treatment that improve pulmonary functions and can be given to active smokers is by giving forward lean position and pursed lip breathing (PLB). Aim : To analize the differences of PEF before and after performing forward lean position and PLB both acute and chronic types in active smokers. Methods: The study was quasi-experimental with pretest posttest, respondents of this study are 18 active smokers with purposive sampling. The instrument used in the research are scales, microtoise and peak flow meter. Method used for data analysis was paired and unpaired t-test. Results: PLB increases PEF with the mean of PEF 28.89±47.08 in acute phase and 28.34±40.84 in chronic phase. The combination of PLB and forward lean position increase PEF with the mean of PEF 30.00±34.91 in acute phase and  46.12±89.60 in chronic phase. Conclusions: There were not statistically significant difference of PEF in acute and chronic phase in group A between before and after intervention (p >0.05). There was not statistically significant difference of PEF in chronic phase in group B between before and after intervention. There was statistically significant difference of PEF in acute phase in group B between before and after intervention.  The combination of forward lean position and PLB showed to have a better effect on increasing the value of PEF than PLB without combination both acute and chronic types in active smokers.Keywords: Pursed lip breathing, forward lean position, peak expiratory flow, active smokers